Hydrological variation and hydro-sediment interrelation of the Luozha River in the Lancang River Basin - Zongyu Li; Zhilin Sun; Lixia Sun; Jing Liu; Wenhua Xiong; Haiyang Dong; Haolei Zheng (Water Supply, 2022)
The research on water and sediment variations is of great importance for regional resource and watershed management. Studying the relationship between precipitation, runoff and sediment load, traditional methods are based on observational data fitted or artificial intelligence predictions, whose accuracy is directly dependent on the quality and quantity of the data. This paper developed a new approach for researching the relationship between precipitation, runoff and sediment load. Based on the sliding accumulative anomaly method, the M-K mutation analysis and the wavelet functions, variation of precipitation and runoff annually were discussed. The results indicated the annual variation trend of the precipitation and runoff have been consistent since 1969, both with a 28-year main cycle, and runoff variations were less subject to human influence in the Luozha River. Therefore, the formula of the relationship between annual runoff and sediment load can be obtained by integrating discrepancy in the magnitude of its variation in the natural state, which was verified by the observational data and was applicable to acquisition of annual sediment load. The current work broadens the current knowledge of recent changes in the Lancang River Basin and improves the recognition of the water-sediment interrelation in the river. HIGHLIGHTS The sliding average accumulation method is proposed to describe hydrological trends.; The correlation between sediment load and runoff was obtained by integrating.; This paper firstly details description of the hydrological variations and the relationship with sediment in the Luozha River of Lancang River Basin.;